2020
DOI: 10.3390/biom10101354
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA as a Biomarker for Coronary Artery Disease

Abstract: Coronary artery disease (CAD) is the leading cause of sudden cardiac death in adults, and new methods of predicting disease and risk-stratifying patients will help guide intervention in order to reduce this burden. Current CAD detection involves multiple modalities, but the consideration of other biomarkers will help improve reliability. The aim of this narrative review is to help researchers and clinicians appreciate the growing relevance of miRNA in CAD and its potential as a biomarker, and also to suggest u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 143 publications
0
20
0
1
Order By: Relevance
“…MiRNAs are biomolecules with a crucial role in the physiological development of the heart and are involved in cardiovascular diseases such as coronary artery diseases (CAD), leading SCD cause in adult subjects [ 7 ], heart failure and left ventricular hypertrophy [ 8 ], atrial fibrillation [ 9 ] and stroke [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are biomolecules with a crucial role in the physiological development of the heart and are involved in cardiovascular diseases such as coronary artery diseases (CAD), leading SCD cause in adult subjects [ 7 ], heart failure and left ventricular hypertrophy [ 8 ], atrial fibrillation [ 9 ] and stroke [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, the alignment of DNA methylation, fragmentome, and topological analysis of cell-free DNA in a targeted or genome-wide manner is expected to have a beneficial impact on clinical practice [ 15 ]. In diseases with metabolic disorders, such as type 2 diabetes [ 16 , 17 ] and coronary artery disease [ 18 ], there are also corresponding cells, such as pancreatic β-cell, whose cell-free DNA fragments are modified, making these cells potential biomarkers of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by He et al, plasma levels of miRNA-21 correlated with several indicators of plaque instability, such as the size of the largest core area, thickness of the fibrous cap, and the lipid pool and the number of macrophages [142]. Several other studies demonstrated that miRNA-21 was upregulated in both patients with ACS and patients with ischemic stroke, as well as in stable CAD [143][144][145]. Apart from miRNA-100, more miRNAs have been recently associated with plaque burden (miR-126, miR-145, miR-155, and miR-29b).…”
Section: Mirnasmentioning
confidence: 99%